Cu(I)‐Catalyzed Asymmetric Cross‐Coupling of N‐Tosylhydrazones and Trialkylsilylethynes: Enantioselective Construction of C(sp)—C(sp3) Bonds. Issue 3 (11th January 2018) - Chu, Wen‐Dao; Guo, Fangfang; Yu, Lefei; Hong, Junting; Liu, Qianyi; Mo, Fanyang; Zhang, Yan; Wang, Jianbo
Abstract : The first catalytic enantioselective C(sp)―C(sp 3 ) cross‐coupling reaction between N ‐tosylhydrazones and trialkylsilylethynes in the presence of Cu(I) salts and chiral phosphoramidite ligands was developed. A series of synthetically interesting, functionalized alkynes were obtained with moderate to good enantioselectivities (up to 83% ee). Cu(II) carbene migratory insertion is proposed to be the enantio‐determining step. Abstract : The first catalytic enantioselective C(sp)—C(sp 3 ) cross‐coupling reaction between N ‐tosylhydrazones and trialkylsilylethynes has been developed. With Cu(I) salt and chiral phosphoramidite ligands, coupling products were obtained with moderate to good enantioselectivities (up to 83% ee).